Pengaruh E-WOM Dan Store Atmosphere Terhadap Keputusan Pembelian Di Fabriek Bloc - Bagas Prasetya; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2024)
E-WOM has become a source of information for consumers in shopping decisions. Meanwhile, store atmosphere is a critical aspect of the consumer shopping experience. The types of data used in this research are primary and secondary data. The population of this study were guests staying at Fabriek Bloc. The research sample consisted of 204 consumers with a sampling technique using non-probability sampling. The data collection technique was carried out using a questionnaire with a Likert scale which had been tested for validity and reliability. Data from this research were processed using SPSS 25.00. The results of this research show that E-WOM is in the quite agree category, namely 2,63%. Furthermore, the store atmosphere variable is in the agree category, namely 2,71%, and purchasing decisions are in the quite agree category with a percentage of 2,72%. The influence of E-WOM (X1) and store atmosphere (X2) influences purchasing decisions (Y), with scores of 65.3% and 34.7% influenced by other factors. Furthermore, the results of multiple linear regression analysis obtained a calculated F value of 191.651 with sig. 0.000 < 0.05, meaning that the E-WOM and Store Atmosphere variables have a significant influence on purchasing decisions, and a t value of 17,423 was obtained for the E-WON variable and a t value of 2,026 for the store atmosphere variable with sig. 0.000 < 0.05.